Elementary excitations in solid oxygen - Freiman, Yu. A.; Jodl, H.J. (Физика низких температур, 2002)
Theoretical results on lattice excitations in solid oxygen at equilibrium vapor pressure are reviewed with the emphasis on the behavior of phonons, librons, and magnons in the orientationally and magnetically ordered α phase. Results on the magnetooptics of solid oxygen and their impact on the advancement of magnetic studies of solid oxygen are briefly reviewed. Some results under discussion are new: among these are theoretical results on the magnon heat capacity, the analysis of the behavior of librons at the α–β transition, and anisotropy of the magons spectrum.